Antibacterial Properties of Pure and Doped Nickel Oxide - S. Nair1, Lakshmi; Balashanmugam2, S.; Rajendrabababu1, K.; Kalaichelvan2, P.T. (Asian Journal of Chemistry, 2013)
The antibacterial behaviour of doped and pure nickel oxide against gram positive and gram negative bacteria has been investigated. Pure and calcium doped NiO have been successfully prepared by a sol gel method without using a capping agent. X-Ray diffraction studies confirm the presence of cubic phase of pure NiO suggesting that the dopants are substituted to the regular Ni sites. The sizes of the samples are determined from the broadening of the XRD peaks. The sizes are found to depend on the dopants added. The morphology of the samples are studied using TEM. All the samples are found to show antibacterial activity. The doped samples are found to exhibit enhanced antibacterial activity against E. coli and Bacillus subtilis.